Modification in induction immunosuppression regimens to safely perform kidney transplants amid the COVID‐19 pandemic: A single‐center retrospective study. Issue 8 (6th June 2021) - Von Stein, Lauren; Witkowsky, Olya; Samidurai, Lakshmi; Doraiswamy, MohanKumar; Flores, Karen; Pesavento, Todd E.; Singh, Priyamvada
Abstract: Background: The COVID‐19 pandemic has negatively impacted organ donation and transplantation across the globe. Methods: This study analyzed transplant outcomes during the pre‐pandemic [PPE, 1/2019–2/2020] and pandemic era [PE, 3/2020–8/2020] based on changes in induction immunosuppression. During PPE, high immunological risk patients received 4–6 mg/kg, moderate risk 2–4 mg/kg, and low risk 1–2 mg/kg of ATG. During PE, ATG doses were reduced to 3–4 mg/kg for high risk, 1–2 mg/kg for moderate, and low changed to basiliximab. Primary outcomes are as follows: biopsy‐proven rejection [BPAR], de‐novo donor‐specific antibody [DSA], delayed graft function [DGF], infection rates, graft loss, and all‐cause of mortality. Results: During PPE, 224 kidney transplants [KTx] and 14 kidney/pancreas transplants [KP] were included, while 180 KTx and 5 KP were included for PE. Basiliximab use increased by 30% in the PE. The odds of DGF were statistically significant between PE vs PPE, OR 1.7 [1.05, 2.8, p ‐value = .042]. The odds of developing DSAs and BPAR during the PE vs. PPE were 0.34 [0.16, 0.71, p ‐value = .004] and OR 0.34 (0.1 to 1.1, p ‐value, .104)], respectively. Cytomegalovirus [19% in PE, 37% in PPE] and BK virus [5.4% PE vs. 16% PPE] incidence reduced during PE vs. PPE. COVID‐19, graft loss, and mortality were comparable between groups. Conclusion: KTx and KP transplants were performed safely during the COVID‐19 pandemic with a reduction of induction immunosuppression.